EFFECT OF CASH MANAGEMENT ON FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Omolara Modinat OMOTUNWASE (Malete Journal of Accounting and Finance)
Deposit Money Banks (DMBs) rely on optimal liquidity to safeguard deposits and invest in profitable ventures, maintaining stakeholders' confidence. However, declining depositor trust, inadequate capital and liquidity, and regulatory sanctions can lead to financial distress and potential insolvency. This calls for investigating the factors influencing DMBs' liquidity and capital adequacy and their impact on banking stability and sustainability. This study examined the effect of cash management on the financial performance of listed deposit money banks in Nigeria for 2013-2022. It adopted an ex-post facto research design with a population and sample size of 14 and 10 DMBs using the judgmental sampling technique; the data were descriptively and inferentially analyzed using regression analysis. Using Panel Ordinary Least Square (OLS) regression as a data estimation technique, the result of the study showed that cash management has a significant effect on return on assets (p-value=0.02629<0.05) and return on equity (p-value=0.01929<0.05). Based on the results, the study concluded that cash management significantly affects the financial performance of listed deposit money banks in Nigeria. The study recommended that deposit money bank management should implement advanced cash flow forecasting models and liquidity management techniques to optimize the allocation of cash reserves and maximize investment returns while ensuring liquidity adequacy